2017
DOI: 10.1016/j.bjpt.2017.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Histological analysis of the association of low level laser therapy and platelet-rich plasma in regeneration of muscle injury in rats

Abstract: HighlightsLLLT and PRP can be used to enhance muscle regeneration.The association of LLLT with PRP produces better treatment than their use in isolation.LLLT could modulate the production of collagen during muscle injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Studies also performed histologic[3,6,8,9,15,17,18,20-25] and gross anatomical[6,15,17,20,21,23] assessments of the muscles (Table 5). Eight studies reported improved functional and structural variables, reduced fibrosis, and increased muscular regeneration in PRP-treated muscle compared to control muscle[6,15,17,20-23,25]. Several studies reported increased angiogenesis after PRP treatment[17,20,21,23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also performed histologic[3,6,8,9,15,17,18,20-25] and gross anatomical[6,15,17,20,21,23] assessments of the muscles (Table 5). Eight studies reported improved functional and structural variables, reduced fibrosis, and increased muscular regeneration in PRP-treated muscle compared to control muscle[6,15,17,20-23,25]. Several studies reported increased angiogenesis after PRP treatment[17,20,21,23].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported increased angiogenesis after PRP treatment[17,20,21,23]. Four studies reported increased leukocyte infiltration at the injection site[8,9,18,25]. With regards to changes in collagen deposition, one study reported increased type III collagen, one reported increased type I collagen[25], and two reported no change in collagen content[2,8].…”
Section: Resultsmentioning
confidence: 99%
“…As possible mechanisms, decreased inflammation and muscle creatine kinase levels are discussed. The combination of LLLT with platelet rich plasma (PRP) produced better results for promoting muscle regeneration after injuries compared to the isolated use of LLLT or PRP [ 118 ].…”
Section: Developing Technologies For Muscle Tissue Engineering Andmentioning
confidence: 99%
“…In particular, PRP injections into skeletal muscles of rats or mice subjected to different traumatic injuries (incision, laceration, contusion or lengthening/eccentric contractions) or to cardiotoxin injection or into ischemic muscles, have been demonstrated to contribute to the muscle healing process: (i) by modulating the inflammatory response including the increase in M2 macrophage cell recruitment to the injury site and function [105,106,107,108]; (ii) by generating a myogenic response, as evaluated by satellite cell activation, increase of the expression of different myogenic regulatory factors, modulation of the expression of muscle specific microRNAs and activation of myogenic signaling pathways leading to myofiber formation [105,106,109,110,111,112,113]; (iii) by attenuating the impairment of myocytes mitochondrial function determined by muscle damage and improving their endogenous antioxidant defense system [114]; and (iv) by protecting cells from apoptosis [108,111].…”
Section: Plasma Preparations: Platelet-rich Plasma (Prp) and Platementioning
confidence: 99%